Winston Churchill. - Haley, Jack, Jr., 1933-2001; Haley, Jack, Jr., 1933-2001; Haley, Jack, Jr., 1933-2001; Noxon, Nicolas, 1936-2016; Wallace, Mike, 1918-2012 (World history in video, 1962)
Winston Churchill, a stubborn, proud, and complex man, a twentieth century symbol of his beloved England. He was destined to lead his nation, late in a lifetime that spanned some of the most crucial years of British history.